2020
DOI: 10.1111/1759-7714.13364
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitor‐associated interstitial lung diseases correlate with better prognosis in patients with advanced non‐small‐cell lung cancer

Abstract: Background Interstitial lung disease (ILD) induced by immune checkpoint inhibitors (ICIs) is a potentially life‐threatening adverse event. The purpose of this study was to evaluate whether the development of immune‐related adverse events (irAEs), especially ILD, was associated with treatment efficacy and to research the features and risk factors of ILD in advanced non‐small cell lung cancer (NSCLC). Methods Between December 2015 and November 2018, 130 advanced NSCLC patients were treated with nivolumab, pembro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 26 publications
(61 reference statements)
3
34
0
1
Order By: Relevance
“…Similarly, BAL CD8+ cells and TILs from this patient exhibited the same expression pattern of PD1 and T-cell immunoglobulin mucin-3 receptor which differed from that of BAL CD8+ cells found in bacterial or chemotherapy-induced pneumonitis [14]. Therefore, BAL findings may also explain the occurrence of CIP in cancers that respond to PD1 inhibitors as we observed in our patients and has been broadly reported [9,15].…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, BAL CD8+ cells and TILs from this patient exhibited the same expression pattern of PD1 and T-cell immunoglobulin mucin-3 receptor which differed from that of BAL CD8+ cells found in bacterial or chemotherapy-induced pneumonitis [14]. Therefore, BAL findings may also explain the occurrence of CIP in cancers that respond to PD1 inhibitors as we observed in our patients and has been broadly reported [9,15].…”
Section: Discussionsupporting
confidence: 80%
“…Thus, severe ICI-ILD may not be a predictive marker of overall survival prolongation in patients with lung cancer. Previous studies have reported the prognostic effect of ICI-ILD, but it is still controversial 11,12 . A recent prospective study reported that ICI-ILD had no effect on prognosis 11 .…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of patients with lung cancer reported that the incidence of ICI-ILD was 14.5%, which is higher than that in clinical trials 11 . ICI-ILD has also been reported to affect the prognosis of patients with lung cancer 11 , 12 . Therefore, ICI-ILD onset is a limiting factor to continue or not continue ICI treatment and to achieve treatment benefits in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A French multi-center retrospective study showed that 3.5% of all patients treated with ICIs developed ICIrelated ILD (ICI-ILD). 14 However, it is more common in patients with lung cancer who are treated with ICIs, with the prevalence reported as 36.8%, 15 13.2%, 16 and 12% 17 in three recent studies. The occurrence of ICI-ILD is more common in males with a history of smoking 14 and is highly associated with pre-existing interstitial lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of ICI-ILD is more common in males with a history of smoking 14 and is highly associated with pre-existing interstitial lung disease. 16,17 ICI-ILD often occurs earlier in lung cancer, with a median of 2.1 months after ICI treatments, 1 and presents as several radiologic patterns. 18 A total of 70-80% of ICI-ILD cases can be controlled through the prompt initiation of a high dose of steroids.…”
Section: Discussionmentioning
confidence: 99%